2018
DOI: 10.1002/ajb2.1082
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of secondary nectar robbing for male components of plant reproduction

Abstract: Combined with prior research, this study suggests that secondary robbing is less costly to a component of male fitness than to female fitness in Ipomopsis, broadening our knowledge of the overall costs of mutualism exploitation to total plant fitness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Costs of primary robbing and, to a lesser extent, secondary robbing have been documented in detail for some plant species, including ones robbed by B. occidentalis at or near our study sites (Irwin & Brody 1998, Irwin & Maloof 2002, Burkle et al 2007. Negative effects can be attributed, for instance, to pollinator avoidance of robbed flowers, direct damage to ovules, and reduced pollen quantity or quality (Irwin et al 2010;Richman et al 2018). In our experimental manipulations of nectar robbing, we found evidence that A. caerulea fruit set was significantly lower when subjected to high rates of robbing, suggesting a potential benefit to the absence of this robber.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Costs of primary robbing and, to a lesser extent, secondary robbing have been documented in detail for some plant species, including ones robbed by B. occidentalis at or near our study sites (Irwin & Brody 1998, Irwin & Maloof 2002, Burkle et al 2007. Negative effects can be attributed, for instance, to pollinator avoidance of robbed flowers, direct damage to ovules, and reduced pollen quantity or quality (Irwin et al 2010;Richman et al 2018). In our experimental manipulations of nectar robbing, we found evidence that A. caerulea fruit set was significantly lower when subjected to high rates of robbing, suggesting a potential benefit to the absence of this robber.…”
Section: Discussionmentioning
confidence: 77%
“…In some well-studied systems, robbing is detrimental to both female and male reproductive function (Irwin et al 2010). In other systems, female function alone is affected (Richman et al 2018). Increased reproductive success resulting from nectar robbing has also been reported, although this appears to be less common than documented negative consequences (Higashi et al 1988;Navarro 2000;Zhu et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies found that nectar robbing can include a cost to the male component of fitness in some species (Castro et al, 2008;Irwin & Brody, 1999;Irwin & Maloof, 2002;Richardson, 2004) but not in others (Maloof, 2001;Morris, 1996;Richman et al, 2018). With the method we used here, it is unclear how much of the pollen released from anthers ultimately reaches stigmas of conspecific plants.…”
Section: Discussionmentioning
confidence: 90%
“…We found that nectar robbing did not negatively affect the male component of reproduction through pollen removal by bumblebees. Other studies found that nectar robbing can include a cost to the male component of fitness in some species (Castro et al., 2008 ; Irwin & Brody, 1999 ; Irwin & Maloof, 2002 ; Richardson, 2004 ) but not in others (Maloof, 2001 ; Morris, 1996 ; Richman et al., 2018 ). With the method we used here, it is unclear how much of the pollen released from anthers ultimately reaches stigmas of conspecific plants.…”
Section: Discussionmentioning
confidence: 95%
“…During nectar robbing, a floral visitor bites a hole in the corolla ("primary robbing") or utilizes an existing hole previously created by another robber ("secondary robbing") to feed from nectar, which often results in no contact with the stigmas or anthers and hence no contribution to pollination (Inouye, 1983;Rojas-Nossa et al, 2016). Some previous studies found limited or no negative fitness consequences of robbing for the plant (Richman et al, 2018;Stout et al, 2000) with some examples of robbing increasing plant fitness through increasing pollen flow and dispersal distance (Higashi et al, 1988;Maloof & Inouye, 2000) and increasing the frequency of visitation from legitimate pollinators (Stout et al, 2000). However, other studies have reported detrimental effects on at least one component of the plant's reproductive success (Adler et al, 2016;Burkle et al, 2007;Castro et al, 2008;Irwin & Brody, 1999;Lara & Ornelas, 2001).…”
mentioning
confidence: 99%